Synthesis and Evaluation of Some Substituted Heterocyclic Fluconazole Analogues as Antifungal Agents - Wang, Shudong; Zhang, Lei; Jin, Yongsheng; Hao Tang, Jin; Su, Hua; Yu, Shichong; Ren, Haixiang (Asian Journal of Chemistry, 2014)
A new series of fluconazole analogues of 1-(1H-1,2,4-triazol-1-yl)-2-(2,4-difluoro-phenyl)-3-4-(substituted-heterocyclic ring-1H-1,2,3-triazol-1-yl)-2-propanols (1-10) were designed, synthesized and evaluated as antifungal agents. Preliminary antifungal tests showed that most of the title compounds exhibited moderate activity with broad spectrum against eight human pathogenic fungi in vitro, compounds 1 and 6 had the best antifungal activity against Candida albicans with the value of MIC80 = 0.5 μg/mL respectively.